Association of muscle disorders in late postmenopausal women according to the type of experienced menopause (2024)
Objective: Musculoskeletal disorders frequently affect postmenopausal women. This study aims to compare muscle disorders between women according to the type of experienced menopause: premature (PM) or normal age of menopause (NAM). Methods: This was a cross-sectional study conducted in nine Latin American countries in which late postmenopausal women (55 to 70 years) were surveyed with a general questionnaire, the Menopause Rating Scale (MRS: item #4 exploring musculoskeletal discomfort), and strength, assistance with walking, rising from a chair, climbing stairs, and falling questionnaire (risk of sarcopenia). Results: A total of 644 women were included: 468 who had NAM, and 176 who had PM (116 spontaneous and 60 surgical). The overall mean age of the participants was 60.9 ± 4.2 years. Women who had PM experienced more musculoskeletal discomfort (33.5% vs 20.9%, P < 0.001) and a higher likelihood of sarcopenia (35.2% vs 19.9%, P < 0.001) than women who had a NAM. Women who had surgical PM exhibited a higher prevalence of severe musculoskeletal discomfort (46.7% vs 29.3%, P < 0.02) and a higher likelihood of sarcopenia (45.0% vs 27.6%, P < 0.02) than women who had a NAM. After adjusting for covariates (age, body mass index, menopausal hormone therapy use, physical activity, education, cigarette consumption, use of antidepressants, sexual activity, comorbidities, and having a partner), our logistic regression model determined that spontaneous PM was not associated with higher odds of musculoskeletal discomfort and higher odds of sarcopenia. On the other hand, women who had surgical PM were more likely to experience musculoskeletal discomforts (odds ratio: 2.26; 95% confidence interval: 1.22-4.17) and higher odds for sarcopenia (odds ratio: 2.05; 95% confidence interval: 1.16-3.65) as compared to women who experienced a NAM. Conclusions: Women experiencing surgical PM have a higher likelihood of developing muscle disorders. This underscores the potential significance of hormonal levels in influencing musculoskeletal health during postmenopause